2017
DOI: 10.1101/lm.045419.117
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between medial prefrontal cortex and dorsomedial striatum are necessary for odor span capacity in rats: role of GluN2B-containing NMDA receptors

Abstract: Working memory is involved in the maintenance and manipulation of information essential for complex cognition. While the neural substrates underlying working memory capacity have been studied in humans, considerably less is known about the circuitry mediating working memory capacity in rodents. Therefore, the present experiments tested the involvement of medial prefrontal cortex (mPFC) and dorsal striatum (STR) in the odor span task (OST), a task proposed to assay working memory capacity in rodents. Initially,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 76 publications
(117 reference statements)
1
17
0
Order By: Relevance
“…For example, a long delay period (at least in the context of WM) exists between the addition of each novel bowl in a given session and rats achieve odor spans much higher than the typical WM capacity limits in humans or primates. These differences have led some authors to question the specific nature of the cognitive function(s) measured by the task (April et al, 2013; Dudchenko et al, 2013; Branch et al, 2014; Davies et al, 2017). This study highlights the diverse and evolving patterns of neural activity observed in the mPFC of rodents performing the OST.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a long delay period (at least in the context of WM) exists between the addition of each novel bowl in a given session and rats achieve odor spans much higher than the typical WM capacity limits in humans or primates. These differences have led some authors to question the specific nature of the cognitive function(s) measured by the task (April et al, 2013; Dudchenko et al, 2013; Branch et al, 2014; Davies et al, 2017). This study highlights the diverse and evolving patterns of neural activity observed in the mPFC of rodents performing the OST.…”
Section: Discussionmentioning
confidence: 99%
“…1 B ) and typically achieve spans of 8 to 15 odors in the task, although higher spans can be attained under some conditions. Performance of the OST depends on a distributed neural circuit including mPFC and dorsomedial striatum but not the hippocampus or posterior parietal cortex (Dudchenko et al, 2000; Davies et al, 2013a,b; 2017; Scott et al, 2018). Span is also impaired by manipulations related to schizophrenia including treatment with NMDA receptor antagonists (Rushforth et al, 2011; Davies et al, 2013a, 2017; Galizio et al, 2013) and maternal immune activation during pregnancy (Murray et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The OST has become widely used in behavioral pharmacology and neuroscience and, following the interpretation of Dudchenko et al (2000), is often represented as providing a rodent model of working memory capacity (e.g., Bratch et al, 2016; Cui et al, 2011; Davies et al, 2017; DeFalco et al, 2019; Rushforth et al, 2010; 2011; Young et al, 2007). In support of this interpretation are findings that accuracy declines as the number of odors to remember increases and that this decline occurs even when the number of comparison choices is held constant across the session (Galizio et al, 2013; MacQueen et al, 2011; Mathews et al, 2018).…”
mentioning
confidence: 99%
“…A growing literature using the OST to analyze drug effects is beginning to identify the neurobiological and pharmacological determinants of performance on this task. For example, OST performance is not affected by hippocampal lesions (Dudchenko et al, 2000), but is impaired by inactivation of the medial prefrontal cortex (Davies, Greba, & Howland, 2013;Davies et al, 2017). Further, the OST was nominated as a benchmark procedure to model working memory capacity in rodents by the CNTRICS group (Cognitive Neuroscience Treatment Research to Improve Cognition in Schizophrenia; Dudchenko, Talpos, Young & Baxter, 2013).…”
mentioning
confidence: 99%
“…More recently we found that two additional non-competitive NMDA antagonists, phencyclidine (PCP) and methoxetamine (MXE), selectively impaired OST accuracy, although the low-efficacy NMDA antagonist ketamine was less selective (Galizio et al, 2016;Mathews, Mead, & Galizio, 2018). Other laboratories have shown that the competitive NMDA antagonist 3-(2-carboxypiperazin-4-yl) propyl-1-phosphonic acid (CPP) produced effects that were similarly selective to OST performance, as did the GluN2B-selective antagonist Ro 256981 (Davies et al, 2013(Davies et al, , 2017MacQueen, Dalrymple, Drobes & Diamond, 2016). Interestingly, these effects generally depend on the number of stimuli to remember.…”
mentioning
confidence: 99%